A Matched Case-Control Study of Noncholesterol Sterols and Fatty Acids in Chronic Hemodialysis Patients - Marek Vecka (MDPI AG, 2021)
Dyslipidemia is common among patients on hemodialysis, but its etiology is not fully understood. Although changes in cholesterol homeostasis and fatty acid metabolism play an important role during dialysis, the interaction of these metabolic pathways has yet to be studied in sufficient detail. In this study, we enrolled 26 patients on maintenance hemodialysis treatment (high-volume hemodiafiltration, HV HDF) without statin therapy (17 men/9 women) and an age/gender-matched group of 26 individuals without signs of nephropathy. The HV-HDF group exhibited more frequent signs of cardiovascular disease, disturbed saccharide metabolism, and altered lipoprotein profiles, manifesting in lower HDL-C, and raised concentrations of IDL-C and apoB-48 (all p < 0.01). HV-HDF patients had higher levels of campesterol (p < 0.01) and β-sitosterol (p = 0.06), both surrogate markers of cholesterol absorption and unchanged lathosterol concentrations. Fatty acid (FA) profiles were changed mostly in cholesteryl esters, with a higher content of saturated and n-3 polyunsaturated fatty acids (PUFA) in the HV-HDF group. However, n-6 PUFA in cholesteryl esters were less abundant (p < 0.001) in the HV-HDF group. Hemodialysis during end-stage kidney disease induces changes associated with higher absorption of cholesterol and disturbed lipoprotein metabolism. Changes in fatty acid metabolism reflect the combined effect of renal insufficiency and its comorbidities, mostly insulin resistance.